Effets d'un dispositif de type coteaching sur le développement professionnel des enseignants novices : études de cas en formation universitaire - Laurent Michel; Stefano Bertone (Nantes Université, 2017)
This study assessed the effects of a coteaching experimentation on the professional development of a preservice teacher (PT) in physical education, during his initial training. By the study of the effects of two coteachings experimentations between a university supervisor and a PT, and following the postulate of Wittgenstein's collective action (2004), this study examined how this experimentation helps the university supervisor to show the meaning of work rules by orders or ostensive action. It also shows that this experimentation encouraged risk taking of PT during their lesson. It shows that this experimentation has been a productive artefact to stimulate the PT's professional development, offering new ways to understand the teacher's apprenticeship in their initial training by block-release training.